ECONOMIC AND ENVIRONMENTAL BENEFITS OF SUSTAINABLE MATERIALS ADOPTION IN AUTOMOTIVE MANUFACTURING - MONDAL, Surajit; GOSWAMI, Shankha Shubhra (Journal of process management and new technologies, 2024)
The automotive industry is undergoing a major transformation towards sustainability, driven by both economic and environmental concerns. Traditional manufacturing processes rely heavily on non-renewable resources like steel and plastics, contributing to environmental degradation and greenhouse gas emissions. However, with increasing regulatory pressures and consumer demand for eco-friendly products, automakers are adopting sustainable materials such as bio-based plastics, recycled metals, and natural fibers. These materials offer environmental benefits by reducing carbon emissions, conserving resources, and minimizing waste, while also providing economic advantages such as improved fuel efficiency, lower production costs, and reduced dependency on volatile resource markets. Integrating sustainable materials often requires changes in production processes, including retooling and new technologies, but these adjustments lead to long-term benefits, such as lighter vehicles, lower energy consumption, and enhanced recyclability. Additionally, innovations like 3D printing have facilitated the use of these materials, allowing for more efficient production with less waste. A lifecycle analysis approach reveals that sustainable materials can significantly reduce environmental impact throughout a vehicle's life, from production to disposal. This shift has also opened up new market opportunities, as consumers increasingly favor vehicles that align with their environmental values. Overall, by adopting sustainable practices, the automotive industry can address both economic and ecological priorities, positioning itself for future growth while leading the way in demonstrating how sustainability can drive innovation.
Keywords: Sustainable materials; automotive manufacturing; environmental impact; fuel efficiency; lifecycle analysis